Onkeno: gender and the emergence of Korubo caciques in the Yaravi Valley - Oliveira Silva, Juliana (2021)
This article examines how the notion of «cacique», introduced through interethnic contact, has been appropriated by the Korubo, speakers of the Pano linguistic family and inhabitants of the Vale do Javari Indigenous Territory, state of Amazonas, in the Brazilian Amazon. Based on the first ethnographic research carried out among the Korubo, it investigates transformations in gender relations that were driven by the interethnic contact with the Brazilian State and indigenous agencies. The article argues that, in the context of this relationship, there is a misunderstanding between the non-indigenous concept of «cacique» and certain authority figures in the daily life of Korubo villages.